Effect of surgical treatment on the anti-tumor immune function in patients with gastric cancer - Bao-Jun Liu (Journal of Hainan Medical University, 2016)
Objective: To explore the effect of surgical treatment on the anti-tumor immune function in patients with gastric cancer. Methods: A total of 50 patients with gastric cancer who were admitted in our hospital from April, 2015 to April, 2016 were included in the study and served as the observation group, while 50 healthy individuals who came for physical examinations were served as the control group. The morning fasting venous blood before operation and 7 d after operation in the observation group and in the control group was collected. FCM was used to detect the levels of CD3+, CD4+, CD8+, CD4+/CD8+, and NK cells (CD16+, CD56+). The immunological function status at different pathological stages before operation and 7 d after operation was analyzed. Results: The expression levels of CD3+, CD4+, CD4+/CD8+, and NK cells in the observation group were significantly lower than those in the control group, while CD8+ level was significantly higher than that in the control group. The expression levels of CD3+, CD4+, CD4+/CD8+, and NK cells before operation were significantly lower than those 7 d after operation, while CD8+ level was significantly higher than that 7 d after operation. The expression levels of CD3+, CD4+, CD4+/CD8+, and NK cells before operation in patients at stage I and II were significantly lower than those in patients at stage III and IV, while CD8+ level was significantly higher than that in patients at stage III and IV. Conclusions: Detection of the expression levels of peripheral blood T cell subsets and NK cells in patients with gastric cancer in the clinic can be served as the important indicator to evaluate the immunological function status, and is of great significance in estimating the condition and assessing the prognosis.